Prehospital emergency rapid sequence induction of anaesthesia. Issue 4 (July 1997) - Graham, C A; Meyer, A D
Abstract : OBJECTIVE: To determine the number of and reasons for rapid sequence inductions done by accident and emergency (A&E) doctors out of hospital as part of the activities of the MEDIC 1 Flying Squad. "Rapid sequence induction" was defined as any attempted endotracheal intubation accompanied by use of drugs to assist intubation and ventilation, including opiates, benzodiazepines, intravenous and topical anaesthetics, and neuromuscular blocking drugs. METHODS: Retrospective study of all MEDIC 1 and A&E records over the period 1 February 1993 to 28 February 1996 (37 months). The anaesthetic technique used, drugs used, complications, difficulties, reasons for induction out of hospital, and grade of doctor performing the technique were determined. RESULTS: Various anaesthetic techniques were used to secure the airway definitively by endotracheal intubation. Several difficulties were encountered in the prehospital setting, all of which were dealt with successfully. CONCLUSIONS: The lack of complications related to rapid sequence induction in prehospital care suggests that this technique is safe when done by A&E doctors on appropriate patients.